Imaging Findings and Treatment Outcomes of Pediatric Rectal Cancers: A Two-Decade Single-Center Retrospective Cohort Study from South India - Stephen, Ruth Anna; Chandramohan, Anuradha; Simon, Betty; Eapen, Anu; Gibikote, Sridhar; Barla, S.S. Ravi Kishore; Mittal, Rohin; Mathew, Leni G. (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Colorectal cancers are rare in the pediatric population.The aim of the study was to describe the imaging findings and staging at presentation in pediatric rectal cancers and to assess the final treatment outcome.Imaging findings, demographic data, histopathology type, and treatment outcomes of patients in the age group of 0 to 18 years who underwent imaging for rectal cancer in the past 20 years were obtained.A total of 18 patients (17 males and 1 female) with a mean (standard deviation [SD]) age of 16.5 (1.3) years and a range of 13 to 18 years were included. On histopathological analysis, 72% (13 cases) had poorly differentiated adenocarcinoma and 83% (15 cases) had either signet ring cells or mucin production. On imaging, 65% (11 cases) were low rectal cancers, 94% had involved circumferential resection margin (CRM), and 29% were positive for extramural vascular invasion (EMVI). Thirty-five percent (n = 6) cases had peritoneal disease. Of the eight patients who were offered neoadjuvant chemotherapy/radiation therapy, 62.5% (n = 5) had inoperable disease on follow-up. Among those who were started on palliative chemotherapy, 38% (n = 3) had disease progression and one patient succumbed to the illness.Pediatric rectal cancers were found to be more prevalent in late childhood/adolescence, with most patients having poorly differentiated adenocarcinoma with signet and/or mucin production. Peritoneal metastasis and EMVI were common in pediatric rectal cancer at presentation, and treatment outcomes were poor.
Keywords: colorectal cancers; adenocarcinoma; pediatric population; peritoneal metastasis; follow-up